POST-OPERATIVE COMPLICATIONS FREQUENCY IN PATIENTS UNDERGOING EMERGENCY LAPAROTOMY IN TERTIARY CARE HOSPITAL - NAZIR, MT; ANJUM, IH; KHARL, RAK; MENGAL, MZ (Biological and Clinical Sciences Research Journal, 2024)
One of the most frequent surgical procedures performed by general surgeons is laparotomy. Early diagnosis and prompt treatment of postoperative complications are the goals of appropriate post-operative care. Objective: The study aimed to explore Post-operative complications frequency in individuals undergoing emergency laparotomy in tertiary care hospitals. Methods: This hospital-based, single-centre longitudinal prospective observational study was carried out at the Surgical Unit 2 SIMS/ Services Hospital Lahore from January 2022 to January 2024 after getting permission from the ethical board. A total of 254 participants in the general surgical unit for emergency laparotomies were included. A thorough medical history of each individual was collected. Participants were followed for post-operative issues and mortality with risk variables after surgery. Clavien-Dindo and severity classifications were used to categorize post-operative issues. Data was entered into Microsoft Excel and presented in the form of tables and figures. Results: A total of 254 individuals took part in this study out of which male were 57(22.44%) and female were 197(77.55 %.). The most prevalent age group in the study participants was 40 to 59 years group 108(42.5%). Gastrointestinal perforation accounts for 80 (31.49%) of the reasons for an exploratory laparotomy, subsequently followed by duodenal perforations 40 (15.7%), gallbladder perforation 30 (11.8%), blunt & penetrating trauma abdomen 15 (5.9%), and appendicular abscess 14 (5.5%). Surgical site infection was the most frequent of these, 120 (47%), followed by fever 97(38.1%) and pneumonia 76 (30 %), thrombophlebitis 27 (10.8%), after surgery ileus 32, (12%), UTI 25 (10%), and nausea and vomiting 35(14%). The mortality rate in our study was 7 %.Conclusion: The current study concluded that emergency laparotomies are more likely to result in postoperative complications than elective ones. The most frequent negative outcomes include fever, vomiting nausea, and postoperative surgical site infection. The overall mortality rate in our study was 7%.